An In-Depth Analysis of Advanced Practice Nurses' Roles in Telemedicine: Evaluating the Impact of Artificial Intelligence on Healthcare Delivery and Patient Outcomes - Albalwi , Wasayif Atallah; Albalawi , Shaymaa Atallah; Mikhizne , Swasan Ibrahim Ahmed; Aldhafeeri , Huda Khalid Ajmi; Alshahrani, Samar Nasser; Alotabi, Suhail Matla; Alotaibi, Tayser Naser Monif; Al Yamani, Najal Mohammed; Albeladi, Ahlam Saleh; Al-Otaibi, Latifa Faihan Ayad; M Alfayez, Abdulmajeed Abdulaziz; Alotaibi, Abdulaziz Abdullah Faisal; et al. (Journal of Ecohumanism, 2024)
Background: The rise of telehealth, particularly during the COVID-19 pandemic, has transformed healthcare delivery, providing essential services to patients in remote areas. Advanced practice nurses (APNs) are crucial in utilizing telemedicine to enhance patient care. However, the integration of artificial intelligence (AI) in telehealth remains underexplored. Methods: This scoping review examines the role of advanced practice nurses in telemedicine, focusing on AI-assisted interventions. A systematic search was conducted across six databases, including PubMed and CINAHL, for studies published from 2017 to 2023. The review assessed user satisfaction, perceptions of AI technology, and the effectiveness of AI algorithms in telehealth applications. Results: The review synthesized findings from eight studies that utilized AI technologies in telehealth for nursing practice. The results indicate that AI tools, particularly machine learning algorithms, significantly enhance decision-making and patient outcomes. APNs reported improved patient monitoring and satisfaction levels with AI-assisted telehealth services. However, challenges such as inadequate training and technology acceptance among nurses were identified. Conclusion: The findings underscore the pivotal role of advanced practice nurses in leveraging AI technologies within telemedicine to improve healthcare delivery. Enhanced training and support for APNs are essential to fully realize the potential of AI in telehealth